2014
DOI: 10.1177/0165551514538151
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on the evaluation of interlinking tools on the Web of Data

Abstract: The rise and widespread use of Linked Data has encouraged data providers to publish and link their content in order to classify and organize information in a useful fashion. Interlinking between datasets enhances data navigation and facilitates searching. As a result, the use of interlinking tools as a way of connecting data items to the Linked Open Data cloud has become more prevalent. In this paper, we examine the results obtained by three interlinking tools used to link a large educational collection to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…We transformed them into a relational database and accordingly we exposed the metadata records as LD using the D2RQ service (Bizer, ), which is a mapping tool for accessing relational databases without having to replicate them into an RDF store. In a previous study (Rajabi, Sicilia & Sanchez‐Alonso, ), we illustrated how the IEEE LOM elements are mapped to RDF according to LD patterns (Dodds & Davis, ). In particular in the mentioned research, we created an ontology (http://data.organic-edunet.eu/lom_ontology_organicEdunet.owl) in which we defined how each learning metadata element is represented as RDF.…”
Section: Methodology and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We transformed them into a relational database and accordingly we exposed the metadata records as LD using the D2RQ service (Bizer, ), which is a mapping tool for accessing relational databases without having to replicate them into an RDF store. In a previous study (Rajabi, Sicilia & Sanchez‐Alonso, ), we illustrated how the IEEE LOM elements are mapped to RDF according to LD patterns (Dodds & Davis, ). In particular in the mentioned research, we created an ontology (http://data.organic-edunet.eu/lom_ontology_organicEdunet.owl) in which we defined how each learning metadata element is represented as RDF.…”
Section: Methodology and Discussionmentioning
confidence: 99%
“…Having the above datasets, we focused on a tool that performs the interlinking task effectively. According to our previous study (Rajabi et al , ), LIMES (Ngonga & Sören, ) is a promising tool in this context and thus can be used for link discovery between Organic.Edunet and the selected datasets. LIMES generates links between items contained in two datasets based on a configuration file set by users.…”
Section: Methodology and Discussionmentioning
confidence: 99%
“…The aforementioned studies have demonstrated that several fundamental works have been carried out in this direction and data publishers can trust the interlinking tools to interconnect their contents to other datasets [12]. However, none of the mentioned studies investigates an interlinking approach between an educational repository and several e-learning datasets on the Web of Data.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In a previous study [12], we evaluated several interlinking tools on the Web of Data and demonstrated that LIMES [17] is a promising tool in this context. In LIMES, a user specifies the endpoints of datasets, comparable entities and thresholds of acceptance of output.…”
Section: Experimental Settingmentioning
confidence: 99%
“…Afterwards, an external interlinking module can be used to link external resources [54]. A complementary study on how interlinking tools can help data publishers to connect their resources to the Web of data can be found elsewhere [39].…”
mentioning
confidence: 99%